Kualitas Pelayanan Pembuatan Sertifikat Tanah pada Kantor Pertanahan / Badan Pertanahan Nasional Kota Palangka Raya - Raden Biroum Bernardianto; Pipit Fitriyah (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2018)
So far there are still many community perspectives that to administer land certificates requires expensive, long time, complicated and convoluted procedures and the completion of land certificates that are not on time is still not by SOPs, so the results are not optimal. The purpose of this study was to determine the quality of land certificate services provided by the National Land Agency (BPN) to the community. This study uses a type of qualitative research. Based on the results of the study, it can be explained that the Land Office / National Land Agency of the City of Palangka Raya in providing services is sufficient to provide excellent quality services because it is seen from the whole as good even though there are still people who are not satisfied with the services of officers. To find out the service quality of the issuance of the land certificate, the writer uses five dimensions, namely: tangible, reliability, responsiveness, assurance and empathy. It is recommended and expected that Palangka Raya City Land / National Land Agency will further improve the quality of land certificate services and prioritize attention to improving service quality on the timeliness of services where officers are expected to be more timely in starting service activities. As well as the timeliness of completion of land certificate services by existing SOPs.